Synthesis and Evaluation of Schiff Bases of 4-Amino-5-(chlorine substituted phenyl)-4H-1,2,4-triazole-3-thione as Antimicrobial Agents - Devkota, Kishor; Pathak, Govinda; Shakya, Bhushan (Journal of Nepal Chemical Society, 2020)
Triazole ring system has attracted a continuously growing interest of synthetic organic chemists and those dealing with the medicinal compounds due to its versatile potential to interact with biological systems. Schiff bases are also considered as one of the most biologically active compounds.  The aim of the present study was to synthesize new Schiff bases bearing triazole nucleus and to assess their antimicrobial activities. Four new Schiff base derivatives of 1,2,4-triazole-3-thione were synthesized by combining two different pharmacophores viz. triazole nucleus and Schiff base moiety and were characterized by spectral techniques (UV, FT-IR, and NMR). The Schiff bases were evaluated for antibacterial (Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae) and antifungal (Candida albicans) activities. The synthesized compounds exhibited good to moderate activities against different strains of bacteria and fungi tested.